"Still Raining, Market Still Rotten": Homeless Men and the Early Years of the Great Depression in Vancouver - McCallum, Todd (Queen's University, 2005)
Single transient homeless men are one of the archetypal figures of the chaotic decade known as the Great Depression. They are also a misunderstood group, commonly associated with a degraded and hopeless existence. This thesis focuses on homeless men, both on the road and in Vancouver, in the period from the fall of 1929, with the collapse of North American stock markets, until the spring of 1932, with the breakdown of the provincial government's relief camp scheme. It argues that those involved in the relationships of charity provision, whether homeless recipient or government bureaucrat, characterized the world of relief with the same terms they used to understand the normalized world of the capitalist economy. Homeless transients flocked to Vancouver by the thousands. Many became the rank-and-file backbone of Communist-led protest movements. Consistently, these movements demanded relief at union rates, challenged the gendered, racial and national categories that divided the unemployed, and rejected outright the oppressive relief measures accorded transients. In response, the municipal government sought to introduce Fordist methods of business management, rationalizing the processes of relief provision with an eye to efficient administration and surveillance. Relief was not a one-sided transaction-a gift from one party to another-but an exchange. When offering the poor food, shelter, fuel and clothing, public and private charities became involved in commercial relationships with the city's service industries. Businesses across Vancouver clamoured to get their share of relief money, hoping to translate some of the money spent on the unemployed into profit. With state-run relief camps, governments created one of the sharpest contradictions of the 1930s, unemployed workers who worked for a living, but for substandard rates of relief. Officials seized upon the crisis to initiate a program designed to develop British Columbia's economic infrastructure. The work of the jobless would thus pay dividends by enabling an increased rate of economic growth once the crisis had passed. In these ways, relief became an industry. The hundreds of people who wrote about tramps during the 1930s twinned the objectification and the commodification of transiency. Whether espousing a humanitarian or a hateful view of hoboes, these authors almost unanimously agreed that the tramping life had to be destroyed. Hoboes would vanish from the Canadian landscape because their lives were without value. For their part, the hoboes who put words on paper ranged across a host of subjects pertaining to life on the road and life in the city. While some cried out against what they saw as the oppressions of transient life and envisioned a future in which they would be reintegrated into society, others lauded the camaraderie and mutuality amongst tramps. For this group, the hobo life was an end in itself, valued because it enabled them to live free from the exploitation that was the lot of wage workers.
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Industry, Ideology, and Social Formation in British Columbia, 1849-1885 - Morton, Jamie (University of Victoria, 2005)
This study examines how the systems of production of the commodity exporting industries of pre-1885 British Columbia contributed to the social formation of the region. Such industries provided the economic base for post-contact development and non-Native settlement of the region, mediated by the cultural values of immigrant and indigenous populations. The intent here is to synthesize a more inclusive model to clarify how these economic and cultural factors intersected to produce a distinct regional society. Beginning with Ian McKay’s suggestion to interpret the history of Canada as a process of naturalizing the liberal order, this study moves the analysis away from microstudies of individual industries or social groups in order to emphasize the way in which a broader vision became naturalized. This approach avoids some of the simple dichotomies of class and race that have informed much of the historiography of BC, in favour of a more nuanced analysis that emphasizes the negotiated process that leads to social consensus. Beginning with the merchant capitalist relations of the fur trade, and accelerating with the 1858 gold rush, BC became understood as a place that provided opportunities for economic and social mobility through participation in commodity exporting ventures. A consensus emerged that emphasized the producer ethic [the economic and cultural value of independent producers], and the creation of a meritocratic socio-political environment to support opportunities for achieved, rather than ascribed, social position. This attracted Euro-North American immigrants hoping to escape social restrictions or proletarianization by achieving independent producer status. Such a goal meant that these immigrants resisted waged labour, creating a chronic shortage that impeded industrial development. This was filled with Chinese immigrants or Aboriginal participants, attracted by the prospect of converting earnings into increased status in their originating societies. Combining the demand for labour with racial ideology, certain jobs were racialized, and BC industries were typified by split labour markets, with an upper echelon comprised of occupationally-mobile Euro-North American workers, and a lower echelon defined by race as well as skill, with little opportunity for mobility. In turn, this contributed to naturalizing ideology concerning race, class, and social position. The emphasis on the producer ethic contributed to an artificial division between “producers” and “agents,” with the former celebrated, while the latter, arguably more important to the systems of production by providing links to export markets, are portrayed less favourably. A commodity exporting, producer-centric variant of the liberal order was naturalized in nineteenth century BC, providing the logic for social and political development, and explaining how certain groups were valued, and either integrated into or excluded from hegemonic society. The degree to which individuals or groups conformed to the naturalized values of the emerging society largely determined their social position in the nineteenth century, and their subsequent treatment in the historiography.

From Conquest to Capitalism: The State, Class, and Capital in British North America, 1760-1860 - Peters, John (York University, 2005)
This thesis traces the transformations in state, class, and politics in British North America from 1760-1860, and how these facilitated the emergence of wider economic change. Building on recent studies in political economy, Marxist and economic history, as well as historical sociology, it employs a class power model of historical change to explain how and why colonial Canada's political economy developed. The argument also draws upon comparative political economy to highlight how different class structures and different forms of political institutionalization shaped political economic regimes and long-run forms of economic growth. The case study analysis of British North America within a wider comparative context demonstrates that class interests, institutions, and policy making were critical to state building and changes in state-society relations, above all to state 'autonomy' and class 'embeddedness'. Agrarians and commercial classes struggled over economic benefits and the reins of political power. But how these classes forged coalitions and how their conflicts were institutionalized within the state determined whether or not new productive dynamics emerged. By the mid-19th century, with greater autonomy, colonial governments across the North American colonies designed institutions, laws, and policies to improve taxation, build infrastructures, enhance the rule of law, and extend the contractual equalities necessary to commercialize the economy. With greater class embeddedness, broader class coalitions of agrarians and merchants actively reshaped agrarian property and agricultural labour to conform to the structures of a market economy, and enacted new market law to allow for the expansion of free labour markets, trade, commerce, and small manufacturing. Looked at comparatively, the thesis claims, 19th century colonial British North America emerged as a 'Liberal Settler' society, led by a diverse coalition of agrarians and merchants. Despite its many state and class particularities, this crystallization of settlers, merchants, and Imperial market-directed politics made colonial Canada a variant of Britain's own liberal political economy, and very similar to other growing settler countries such as the United States. Exploring the connections between state, class, and politics, the thesis concludes, can tell us much about why and how these distinct historical patterns emerged, and why 19th century political economies changed in ways that fostered the development of capitalism.
Keywords: Capital; Capitalism; Conquest; Political economy

The Making of CUPE: Structure, Democracy and Class Formation - Ross, Stephanie (York University, 2005)
This thesis explores the nature and challenges of democracy within unions through an historical examination of the emergence and early years of the Canadian Union of Public Employees (CUPE). Formed by a merger of two pre-existing unions in 1963, CUPE casts new light on the Marxist, Michelsian and Institutionalist theoretical approaches to union democracy. The thesis calls into question the narrow and ahistorical link made between centralization, oligarchy and effectiveness on the one hand, and decentralization, democracy and ineffectiveness on the other. Instead, the case of CUPE shows that unions are subject to contradictory pressures and that neither centralization nor decentralization is inherently more democratic. Union democracy is part of an historical process of class formation, in which both union purposes and the boundaries of the democratic community (which can make legitimate claims on members' solidarity and self-discipline) are struggled over. As such, it is possible that decentralizing forces can place narrow and sectionalist priorities over the interests of the broader community. Moreover, the thesis argues that the use of merger as a method of forging greater class unity is itself problematic. The merger which created CUPE involved a protracted struggle over which model of union would prevail. The compromise which was reached entrenched a self-reinforcing cycle of autonomy-seeking by union locals which, over the long term, prevented the development of an effective national union capable of carrying out the democratic will of the membership as a whole. As such, through an historical excavation of the roots of contemporary crises in CUPE, the thesis points to the important way in which the outcomes of past decisions come to structure future political possibilities for unions and other social justice organizations.
Keywords: Canadian Union of Public Employees; Class formation; Democracy; Labor Unions; Social sciences

Oshawa Autoworkers: Social Integration and Oppositional Class Consciousness Among the Unionized Workers of General Motors - Roth, Reuben N. (University of Toronto, Ontario Institute for Studies in Education, 2005)
Many social theorists (Goldthorpe, Lipset, Giddens, Hout, Brooks and Manza) have portrayed members of the Western industrial working-class as accommodative and resistant to a class-based social revolution. They suggest that an affluent proletariat has seen its oppositional class-consciousness subverted and transformed by the 'cash nexus' into various forms of social integration. With reference to Mann's (1973) measures of class-consciousness typologies and Livingstone and Mangan's (1996) study of Hamilton steelworkers, I explore expressions of working-class consciousness among organized workers at one of Canada's largest industrial union locals, the Canadian Auto Workers (CAW) Local 222 at General Motors, in Oshawa, Canada. I accomplish this via an examination of the existence and degree of working-class imagery, class identity, and oppositional working-class consciousness among this group of workers on the basis of measured responses to a survey questionnaire (N=102), in-depth interviews, and participant observation. My thesis asserts that Oshawa autoworkers' material advantage is insufficient to transform their proletarian consciousness. I have found that among Oshawa autoworkers there is a shared view of Canadian society as class-based, a clear working-class self-identification and measurable forms of oppositional working-class consciousness.
Keywords: Autoworkers; General Motors; Ontario; Oppositional class consciousness; Oshawa; Social integration; Social sciences; Unionized

Engaging Women’s History Through Textiles: Enhancing Curricula with Narratives of Historical Memory - Wheeler, Eileen Margaret (University of British Columbia, 2005)
During the late nineteenth and early twentieth centuries, racism, in the form of white supremacy, shaped relations between whites and Chinese British Columbians. In resisting and accommodating to white supremacy, the Chinese were active participants, along with the members of the dominant society, in shaping these relations. White supremacy was consequently a dynamic system, one whose many parts were continually in flux, and whose central constructs—notions of "race" and British Columbia as "a White Man's province"—were largely political in nature. The thesis argues that white supremacy, as both ideology and organization, was deeply imbedded in British Columbia society. Exclusion based on "race" was incorporated into government institutions as they were remade at Confederation in an effort to enhance the power of white male property-owners. By the early twentieth century, ideological constructs of "the Chinaman" and "the Oriental" were used as foils in the creation of identities as "whites" and as "Canadians." The official public school curriculum transmitted these notions, while schools themselves organized supremacy in practice by imposing racial segregation on many Chinese students. In reaction, the Chinese created their own institutions and ideologies. While these institutions often had continuities with the culture of South China, the place of origin of most B.C. Chinese, they were primarily adaptations to the conditions of British Columbia, including the realities of racism. Chinese language schools played an especially important role in helping to create a Chinese merchant public separate from the dominant society. This public was at once the consequence of exclusion and the greatest community resource in resisting white supremacy. The study concludes by questioning the workability of contemporary anti-racist strategies which treat racism as a marginal phenomenon, or as merely a set of mistaken ideas. Instead, it suggests that such strategies must recognize that racism is one of the major structures of Canadian society.